Covidscapes: The Pandemic in the Philippines - Aguilar Jr., Filomeno V.; (Archīum Ateneo, 2020)
This introductory essay develops the notion of Covidscapes, taking a cue from Arjun Appadurai. Despite mutations, a single type of coronavirus has gone around the world causing the Covid-19 disease. Yet experiences with the pandemic have varied widely across and even within countries for reasons that go beyond the pathogen. The concept of Covidscapes captures the simultaneous sharing of a global phenomenon along with diversity and difference. Covidscapes are profoundly perspectival and disjunctive. State–societal factors suggest countries can have their own Covidscapes. The contributions in this issue shed light on the peculiar dynamics and contradictions of the Philippine Covidscape. KEYWORDS: COVID-19 • MIGRATIONS • HISTORY • STATE RESPONSE • MUTUALITY • ETHICS OF CARE